Matters of fact in Jane Austen : history, location, and celebrity - Barchas, Janine (The Johns Hopkins University Press, 2012)
"Matters of Fact in Jane Austen: History, Location, and Celebrity makes the bold assertion that Jane Austen's novels allude to actual high-profile politicians and contemporary celebrities as well as to famous historical figures and landed estates. Janine Barchas is the first to conduct extensive research into the names and locations in Austen's fiction by taking full advantage of the explosion of archival materials now available online. According to Barchas, Austen plays confidently with the tantalizing tension between truth and invention which characterizes the realist novel. Of course, the argument that Austen deployed famous names presupposes an active celebrity culture during the Regency, a phenomenon recently accepted by scholars. The names Austen plucks from history for her protagonists (such as Dashwood, Wentworth, Woodhouse, Tilney, Fitzwilliam, and many more) were hugely famous in her day. She seems to bank upon this familiarity for interpretive effect, often upending associations with comic intent. Barchas re-situates Austen's work nearer to the historical novels of her contemporary Sir Walter Scott than to the domestic and biographical perspectives that until recently have dominated Austen studies. This forward-thinking and revealing investigation offers scholars and ardent fans of Jane Austen a wealth of juicy historical facts, while shedding an interpretive light on a new aspect of the work of a much-beloved writer."--Project Muse.